Trabajo infantil, explotación laboral y vulneración del interés superior de los menores en la urbe lojana. - Matailo Paredes, Alex Segundo (2023)
The present Curricular Integration Work has as its name: "Child labor, labor exploitation and violation of the best interests of minors in the city of La Paz", arises from the need to investigate and develop this topic due to recent events in Ecuador, especially in our city where there is evidence of a major problem within the city of La Paz, where we can see at present children, girls and adolescents in child labor and even in labor exploitation, selling vegetables, vegetables, often in begging, clear instability in childhood, We can currently observe children and adolescents in child labor and even in labor exploitation, selling vegetables, vegetables, many times in begging, clear instability in childhood, therefore the principle of the best interest of the child would be violated as these children and adolescents participate in labor activities that are not appropriate for their age, which interfere with their education, physical and psychological development, and that interfere with their physical and psychological development; physical and psychological development, and which often result in labor exploitation. Internationally, there are efforts to eradicate child labor through laws, policies and programs that promote education, child protection and child welfare, it is very important to note that the Constitution of the Republic of Ecuador protects children and adolescents, these groups of high vulnerability, the State, the family and society taking responsibility for their care specifically found in Art. 44, 45 and 46. As each regulation to protect the rights of people has its own code in this case is no exception and we have the Code of Childhood and Adolescence that deals with the issue of child labor in Art. 81 and 83, in addition to this we could compare the existence of policies and programs to eradicate child labor, however there are still children and adolescents in street vending and even begging in the city of La Paz. Child labor and labor exploitation of children and adolescents is a serious problem that, despite being protected by the Constitution of the Republic of Ecuador, the Code of Children and Adolescents and public policies or programs, there are shortcomings. With the present investigation it is possible to determine that children and adolescents of the city of La Paz who perform street vending, present a violation of their rights since these activities limit their time to perform productive activities such as attending school or recreational activities, in addition these forced activities are not in accordance with their age, nor with their physical and psychological development.